Low back pain presentations to rural, regional, and metropolitan emergency departments. (1st March 2022) - Davidson, Simon R. E.; Kamper, Steven J.; Haskins, Robin; O'Flynn, Michael; Coss, Karen; Smiles, John Paul; Tutty, Amanda; Linton, Jane; Bryant, Joe; Buchanan, Maree; Williams, Christopher M.
Abstract: Objective: To describe the context of low back pain (LBP) presentations to emergency departments (EDs) by remoteness areas, hospital delineation level and staffing portfolios. Design: A retrospective observational study using routinely captured ED and admission data over a 5‐year period (July 2014–June 2019). Settings: Thirty seven EDs across a large health district in NSW, Australia, covering major cities, inner regional areas and outer regional areas. Participants: Emergency department (ED) presentations with a principal or secondary diagnosis of LBP based on ICD‐10 code (M54.5). Main outcome measures: ED presentation and associated admission measures, including presentation rate, referral source, time in ED, re‐presentation rate, admission details and cost to the health system. Results: There were 26 509 ED presentations for LBP across the 5 years. Time spent in ED was 206 min for EDs in major cities, 146 min for inner regional EDs and 89 min for outer regional EDs. Re‐presentation rates were 6% in major cities, 8.8% in inner regional EDs and 11.8% in outer regional EDs. Admission rates were 20.4%, 15.8% and 18.8%, respectively. Conclusions: This study describes LBP presentations across 37 EDs, highlighting the potential burden these presentations place on hospitals. LBP presentations appear to follow different pathways depending on the ED remoteness area, delineation level and staff portfolio.